Implementing Vocabulary Journal Strategy in Intensive Reading Activities for EFL Vocational Students - Salfarani, Nindyara Aftika; Kamil, Acep Bahrum; Ambarwati, Evi Karlina (Innovative: Journal Of Social Science Research, 2024)
Vocabulary mastery is one of the key components in language learning, especially in the context of intensive reading. Many strategies can be used in vocabulary learning, one of which is vocabulary journaling. While many studies have explored the experiences of upper secondary students, this study explores the experiences of five students in tenth-grade vocational secondary students in using vocabulary journals in intensive reading. This study used a qualitative design with a case study method and used interviews and reflective journals to collect students' experiences in using the vocabulary journal strategy. The data were then analyzed using thematic analysis. The findings of this study revealed that all participants had positive experiences using vocabulary journal strategy in intensive reading. Students revealed that vocabulary journaling improved their vocabulary knowledge and reading comprehension skills. In addition, students are more independent and motivated to learn more about vocabulary. Therefore, vocabulary journaling is an appropriate strategy to facilitate students' learning experience in practicing vocabulary improvement and understanding the content of stories.